Students Critical Thinking Ability to Solve Problems HOTS in Regular, Acceleration, and Olympics Class Programs - Dwi Priyo Utomo; Aci Maria Jehaut Putri; Teguh Santoso (Universitas Syiah Kuala, 2022)
Critical thinking skills are one of the main objectives of learning Mathematics. HOTS questions are needed so that students are familiar with international standard questions. This study aims to describe the mathematical critical thinking skills of students in the Regular, Accelerated, and Olympic class. Qualitative descriptive research approach with case study design. The subjects of this study were three students who came from different class programs. The research instruments used were tests and interviews. Data analysis used the following procedures: reduction data, data presentation, and conclusion drawing. The results showed that the Regular class students had 'low' critical thinking skills. Regular students are still confused about understanding the main idea of the problem, so the strategies used are not appropriate. Acceleration class students have 'good' critical thinking skills. Accelerated students can answer questions briefly and concisely, less thorough in drawing final conclusions. Olympiad class students have 'very good' critical thinking skills. Student answers are complete and clear. Olympiad class students understand the main purpose and objectives of the questions so that they lead to correct procedures and calculations.